Monitoring COVID-19 Impact on Refugees in Ethiopia, Report No. 2 : Results from a High-Frequency Phone Survey of Refugees - Wieser, Christina (World Bank, Washington, DC, 2021)
The World Bank Group, the Ethiopia Agency for Refugee and Returnee Affairs (ARRA), the United Nations High Commissioner for Refugees (UNHCR), and the World Bank-UNHCR Joint Data Center on Forced Displacement (JDC) collaborated to integrate refugees in the ongoing High-Frequency Phone Surveys (HFPS) . The World Bank-led HFPS of households seek to monitor the economic and social effects of the COVID-19 pandemic among Ethiopian nationals and refugees. The main objective is to inform timely and adequate policy and program responses. Since the outbreak of the COVID-19 pandemic in Ethiopia, two rounds of data collection of refugees were completed between September and November 2020. The first round of the joint national and refugee HFPS was implemented between the 24 September and 17 October 2020 and the second round between 20 October and 20 November 2020.